CHAPTER 10: Fluoride in Saliva and its Impact on Health - (:unkn) unknown (Royal Society of Chemistry, 2015)
Saliva is a secretion of the salivary and mucous glands and it has a major role in the maintenance of both general and oral health. Fluoride is an important element of the inorganic content of saliva. Fluoride can be found densely in nature as well as in toothpastes, rinses, lozenges, chewable tablets and drops. Dentists use fluoride in the professional application of gels, foams, and varnishes since it is the main agent that is of help to reduce the prevalence of dental caries. Protective programs for the prevention of dental caries in children should essentially involve the daily use of fluoride. However, fluoride intake must be well balanced between the accurate estimation of caries risks and the possible risks for toxic effects of the fluoride. The fluoride concentration in whole saliva is related to the fluoride excreted from the glands and it also depends on dietary fluid intake and dental fluoride preparations. Fluoride's effects on general health are not well documented, possible claims on cancer, kidneys, brain, fetal development, stomach and endocrine glands have been made in the literature. Fluoride is an important trace element in the maintenance of general and oral health. © The Royal Society of Chemistry 2015.